The Berkeley manuscript (Olim Phillipps 4450): a compendium of fourteenth-century music theory (volumes I and II) - Ellsworth, Oliver Bryant (Michigan University microfilms international, 1984)
Dissertation submitted in partial satisfaction of the requirements for the degree of Doctor of Philosophy in Music in the Graduate Division of the University of Califa-ornia, Berkeley, 1969